An historic step for advanced cytopathology training in Canada. Issue 1 (23rd September 2014) - Auger, Manon; Islam, Shahidul; Weir, Michele
Abstract : Advanced cytopathology training has finally obtained official recognition in Canada, having recently been assigned the newly developed status of "Area of Focused Competence" by the Royal College of Physicians and Surgeons of Canada. It is hoped that the trainees who graduate from these programs in cytopathology will be provided with the leadership and consultant skills to allow them to adapt and respond competently to the rapid evolving field of cytopathology.